Crossability of miniature rose and quantitative and qualitative traits in hybrids - Meral, Ezgi Doğan (Frontiers in Plant Science, 2023)
Potted miniature roses are popular indoor ornamental plants. Due to consumer demands, different varieties are introduced to the market every year. The most widely used method for the development of potted miniatures is cross breeding. Six divergent popular pot miniature roses as female parents and Rosa centifolia and Black Baccara as male parents as well as 190 of their F1 hybrids were studied to determine the extent of crossability and the heterosis effects for several quantitative and qualitative traits for determining miniature rose breeding potential. The percentage of pollen viability and the pollen germination rate differed between 48.61% and 61.27% and between 23.26% and 32.19%, respectively. All cultivars exhibited a strong correlation between the fruit set, the weight of fruit, the total set, the weight of seed, the number of seeds per fruit, and the seed germination rate. The cultivar Rosa White Star as a female parent exhibited a good fruit set and crossing success, whereas Juanita Kordana showed a poor crossing success rate. The maximum setting after the crossing was that of Rosa White Star × R. centifolia comprising 75% of fruits, 132 total seeds, and seed weight of 0.68 g. The highest number of seeds per fruit (12.63) was obtained from Rosa Bling Love Star × R. centifolia, and the Red Romance × Black Baccara had the maximum germination of seed rate (48%). The potential for heterobeltiosis and heterosis varied and exhibited a contrasting performance for various qualitative and quantitative traits between F1 progenies. The parents and F1 hybrids were sorted into three major groups by cluster analysis based on the phenotypic variation.